Conocimientos, actitudes y prácticas de los cirujanos dentistas sobre lesiones bucales como elemento de diagnóstico del maltrato infantil - Quispe Dionicio, Gary Antero (2017)
Objective: The present descriptive and cross - sectional study was to determine the level of knowledge, attitudes and practices of Dental Surgeons on oral lesions as an element of diagnosis of child maltreatment, in the province of Trujillo, in 2016. Materials and methods: The sample consisted of a total of 73 Dental Surgeons, of which 39 (53.4%) are women and 34 (46.6%) are men. Results: The results show that 83.6% of Dental Surgeons have a regular level of knowledge, 91.8% have an adequate level of attitudes; And 53% a good level of practice. Conclusions: It is concluded that the majority of MINSA Dental Surgeons in the province of Trujillo present a regular level regarding knowledge, adequate level in relation to attitudes and good level with respect to practices on oral lesions as an element of diagnosis of child maltreatment.